METHODOLOGY OF USING EDUCATIONAL GAMES IN THE TEACHING PROCESS OF INFORMATION AND COMMUNICATION TECHNOLOGIES (World Bulletin of Education and Learning, 2025)
This study examines the methodological foundations and pedagogical potential of using educational games in the teaching process of Information and Communication Technologies in pedagogical universities. In the context of rapid digitalization of education, ICT courses are expected not only to develop students’ technical competencies but also to foster creativity, critical thinking, collaboration, and learner engagement. Educational games are considered an effective didactic tool that integrates cognitive activity with motivation and practical skill development. The research is grounded in contemporary theories of game-based learning, constructivist pedagogy, and student-centered education, emphasizing the role of interactive learning environments in professional teacher training. The study analyzes how educational games can be systematically integrated into ICT lessons to support the acquisition of theoretical knowledge, the development of practical digital skills, and the formation of pedagogical competencies necessary for future teachers. Special attention is given to the methodological conditions for effective implementation of educational games, including alignment with learning objectives, adaptation to learners’ levels, and the use of digital platforms and software tools. The findings highlight that a well-structured methodology of game-based instruction in ICT enhances learning motivation, improves learning outcomes, and contributes to the professional readiness of future educators for innovative teaching practice in digital learning environments.
Keywords: Educational games, information and communication technologies, game-based learning, digital pedagogy, interactive learning, teacher education, learning motivation, professional competence.